Pegmatite dykes and quartz veins with tourmaline: an example of partial melting in the contact aureole of the Chandman Massif intrusion, SW Mongolia - Burianek,D.; Hanzl,P.; Hrdlickova,K. (Journal of Geosciences, 2011)
Pegmatite dykes with tourmaline and quartz–tourmaline veins in the Chandman Khayrkhan Crystalline Complex (the Eastern Mongolian Altay range, SW Mongolia) are spatially related to the contact aureole of the Variscan granitoids of the Chandman Massif. Tourmalines are also present in pegmatites that intruded into the I-type granitoids of the Chandman Massif near the contact with surrounding migmatites. The fluid-present melting of metapelites in wall rocks of the I-type granodiorites and tonalities can be considered as the main process inducing the boron-rich granitic melt formation. Variations in chemical compositions of tourmaline from several pegmatite dykes, mainly in Na, Ca, Al, Fe and Mg, are interpreted as a result of fractionation of the parental melt. The quartz–tourmaline veins represent a product of crystallization of aqueous fluid exsolved from the pegmatite melt. Chemical compositions of tourmaline with elevated Ca and Mg are interpreted to reflect mixing of the boron-rich postmagmatic fluids with Mg–Ca enriched external component represented by fluids from the biotite-rich metaluminous igneous host rocks.
Keywords: tourmaline; pegmatite; microchemistry; compositional evolution; Mongolian Altay Mts.; SW Mongolia